FRI0153 ULTRA HIGH-RESOLUTION ULTRASOUND (UHFUS) OF LABIAL SALIVARY GLANDS: POTENTIAL APPLICATIONS IN PRIMARY SJÖGREN'S SYNDROME. (2nd June 2020) - Baldini, C.; Ferro, F.; Izzetti, R.; Vitali, S.; Fonzetti, S.; Governato, G.; Aringhieri, G.; Elefante, E.; Mosca, M.; Donati, V.; Caramella, D.
Abstract : Background: Major salivary gland ultrasonography has an established role in diagnosis and assessment of pSS. Nowadays, however, interest is also growing in last-generation ultra high resolution ultrasound (UHFUS) transducers, which can produce frequencies up to 70 MHz and achieve tissue resolution up to 30 μm, opening up new possibilities for the study labial salivary glands (LSG). Objectives: To investigate the usefulness of UHFUS in LSG ultrasound-guided biopsy and preoperative planning. Methods: Consecutive patients undergoing a LSG for clinically suspected pSS were included in this study from January 2018 to December 2019. UHFUS of LSG was performed by using VEVO MD, equipped with a 70 MHz probe, scanning first the central compartment of the inferior lip, and then both peripheral compartments. The following parameters were evaluated: distribution of the glands, parenchymal inhomogeneity (score 0-3, from normal to evident), and fibrosis. UHFUS imaging was used to help locate the LSG for the US-guided biopsy. The same expert pathologist calculated the surface area of gland sections examined, the LSG focus score (FS), the number of foci and evaluated the presence of ectopic germinal centers (GCs). Consecutive patients that had undergone a traditional LSG biopsy from December 2016 to December 2017 were included as controls. Results: We included a total of 249 patients with suspected pSS: 137 undergoing the UHFUS-guided LSGs and 112 the traditional LSG biopsy procedure. No demographic differences were observed between the two groups. No differences were also observed in the distribution of the final diagnosis. A diagnosis of pSS according the ACR 2016 criteria was made in 60/137 (43.8%) and 36/112 (32.1%) patients, respectively whereas a diagnosis of no-SS sicca was made in 44/137 (32.1%) and in 43/112 (38.4%) patients; the remaining diagnosis included secondary SS (4/137, 3% and 9/112, 8%) and undifferentiated connective tissue disease (UCTD) (29/137, 21.2%, and 24/112, 21.4%). With respect to no-SS sicca controls and UCTD patients, pSS patients presented higher UHFUS inhomogeneity scores in both central and peripheral labial compartments (p=0.001). There were no complications from the HUFUS-guided LSG biopsy. The mean glandular surface area obtained was significantly higher than the area obtained by traditional LSG biopsy procedure (7.4 ±4.0 mm 2 vs 6.3±3.7 mm 2, p=0.02) thus facilitating the assessment of the FS. Interestingly, the latter showed a good correlation with the UHFUS inhomogeneity (r=0.509**, p=0.000). Conclusion: UHFUS of LSG appeared feasible and sensitive in pSS, potentially offering unique advantages in LSG ultrasound-guided biopsy. Disclosure of Interests: None declared